Market sccess and home market effect - Dionysios Karavidas (Open Economics, 2020)
Based on the standard Footloose Capital model developed by Martin and Rogers (1995), I consider an integrated model that consists of a system of two regions and a third external region, in order to study the impact of improved market access on the Home Market Effect within the system of the two regions. The concept of the Home Market Effect is well known in the literature, but once we extend the number of regions, many are unknown. The main finding of the model suggests that improved market access with respect to an external market enhances the Home Market Effect within the system of the two regions. Interestingly, I show that this finding comes from the fact that improved market access increases the Market Access Effect, while it has no impact on the Market Crowding Effect.
Keywords: F02; F22; F06; R12; 330; Market Access; Home Market Effect; Footloose Capital; Internal Geography